Evaluation of Streck Tissue Fixative, a Nonformalin Fixative for Preservation of Stool Samples and Subsequent Parasitologic Examination - Nace, Eva K. (American Society for Microbiology, 1999)
We undertook a study to evaluate Streck tissue fixative (STF) as a substitute for formalin and polyvinyl alcohol (PVA) in fecal preservation. A comparison of formalin, PVA, (mercuric chloride based), and STF was done by aliquoting fecal samples into each fixative. Stool specimens were collected in Haiti, and parasites included Cyclospora cayetanensis, Giardia intestinalis, Entamoeba coli, Iodamoeba butschlii, Endolimax nana, Ascaris lumbricoides, Trichuris trichiura, Strongyloides stercoralis, and Necator americanus. Preserved stools were examined at various predetermined times (1 week, 1 month, and 3 months) to establish the quality of the initial preservation as well as the suitability of the fixative for long-term storage. At each time point, stool samples in fixatives were examined microscopically as follows: (i) in wet mounts (with bright-field and epifluorescence microscopy), (ii) in modified acid-fast-, trichrome-, and safranin-stained smears, and (iii) with two commercial test kits. At the time points examined, morphologic features remained comparable for samples fixed with 10% formalin and STF. For comparisons of STF- and 10% formalin-fixed samples, specific findings showed that Cyclospora oocysts retained full fluorescence, modified acid-fast- and safranin-stained smears of Cryptosporidium and Cyclospora oocysts were equal in staining quality, and results were comparable in the immunofluorescence assay and enzyme immunoassay commercial kits. Stool fixed in STF and stained with trichrome showed less-than-acceptable staining quality compared with stool fixed in PVA. STF provides an excellent substitute for formalin as a fixative in routine examination of stool samples for parasites. However, modifications to the trichrome staining procedures will be necessary to improve the staining quality for protozoal cysts fixed in STF to a level comparable to that with PVA.